Efectos de la asociación Micorrizas más Trichoderma sobre el crecimiento de plántulas de cacao (Theobroma cacao) en viveros, en la zona de Babahoyo - Lucas León, Jossel Agustín (2016)
VIII. SUMMARY The present investigation was made in the lands of the experimental farm "San Pablo" that is located in the km 7,5 of the road Babahoyo-Montalvo. The objective of the investigation was to evaluate the effect of the association more Micorrizas Trichoderma about the growth of plants of cocoa in nurseries, in the area of Babahoyo. Included ten treatments were investigated a witness with three repetitions, distributed at random in a design of blocks. For the evaluation of stockings the test was used from Duncan to 95% of probability. At the end of the cycle of the cultivation plant height, diameter of shafts, emission was evaluated to foliate, root longitude, radical biomass, colonization percentage, density of the endófito and count of spores. The results determined that the application of ANCUPA 1 + CUSTOM GP in dose of 15 cc product in the sustrato, the growth increased with increments of 15-37% with relationship to the witness. In the same way to apply ANCUPA 1 + CUSTOM GP, impacted in the evaluated variables, except for diameters of shafts and radical biomass.